Upaya Kerja Sama Multilateral Indonesia dalam Menanggapi Kebijakan Red Ii Uni Eropa - Deitra Aisha; Akim Akim (Syntax Corporation, 2023)
Indonesia has the largest palm oil plantation industry and is the world's largest producer of palm oil. Palm oil commodities originating from Indonesia are exported to almost all continents with the highest consumers found in the Asian continent and the European Union region. The European Union as one of the major consumers of Indonesian palm oil in 2018 revised its policy to Renewable Energy Directive II (RED II) which reaped negative sentiment towards the Indonesian palm oil industry. Then, the Government of Indonesia responded to these negative issues through several diplomatic efforts, such as multilateral cooperation. This article discusses Indonesia's trade diplomacy activities to the European Union using multilateral cooperation. This research uses qualitative research methods with the concept of economic diplomacy The data used in this study was obtained using several data collection techniques, such as literature studies. These data are analyzed and discussed using the framework of economic diplomacy concepts to explain the economic diplomacy activities carried out by Indonesia to the European Union on its palm oil commodities by joining multilateral cooperation. The result of this study is that Indonesia in making efforts to maintain its palm oil follows several bilateral and multilateral cooperations such as its participation in CPOPC.